Adipose-derived mesenchymal stem cell therapy in the treatment of knee osteoarthritis: a randomized controlled trial. (14th February 2019) - Freitag, Julien; Bates, Dan; Wickham, James; Shah, Kiran; Huguenin, Leesa; Tenen, Abi; Paterson, Kade; Boyd, Richard
Aim: To evaluate the efficacy of autologous adipose-derived mesenchymal stem cell (ADMSC) therapy on pain, function and disease modification in knee osteoarthritis.Methods: 30 participants with symptomatic knee osteoarthritis were randomized into three groups. Two treatment groups received intra-articular ADMSC therapy consisting of either a single injection (100 × 10 6 ADMSCs) or two injections (100 × 10 6 ADMSCs at baseline and 6 months). The third group served as control and continued conservative management.Results: No serious adverse events were observed. Both treatment groups receiving ADMSCs showed clinically significant pain and functional improvement at completion of follow-up at 12 months. Radiological analysis using the Magnetic Resonance Imaging Osteoarthritis Knee Score indicated modification of disease progression.Conclusion: Autologous ADMSC therapy appears to be a safe and effective therapy for knee osteoarthritis and may have the potential to prevent disease progression. Trial registration number: ACTRN12614000814673